Technogenic Transformations of Sea Coasts on the Example of the Baltic Sea - Bogdanov, N.A; Paranina, A.N (International Journal of Geography and Geology, 2016)
Natural and technogenic factors of violation of natural development of the Liepaja sandy rerash in Southeast Baltic are considered. Along coast for many years there has been a stream of substance and energy, unidirectional to the North. At the beginning of the 20th century after the reconstruction of the Russian port of Libava and lengthening of piers for more than 2 km, a stop of sea deposits along the coast appeared. It caused catastrophic local washout of the coast and bottom. In result, territorial losses, beach titanium-zirconium rerash, different types of pollution appeared. By a research it was established: 1. Rate of abrasion (20th century the coast receded to 200 m); 2. Formation and dynamics of the centers of concentration of heavy minerals, is defined amount of the useful ore minerals in a productive size of beach sands (0,2-0,25 mm, an ilmenite, a magnetite, zircon, rutile, a monocyte, leucoxene; 74% or 1523 kg/m3); 3. Major factors of change of a condition of coast and bottom of the sea. Also an assessment of consequences is given to events of World War II and on the Chernobyl NPP. Illustrations of the article show localization of concentrates of heavy minerals in a ledge of washout of the coast and on the beach, and also structure of mean annual coastal streams of substance and wave energy in technogenic morpholytho-dynamic anomaly at the port of Liepaja.